2008
DOI: 10.1371/journal.pone.0003381
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Promotes Pathological Angiogenesis by Regulating Macrophage Response to Hypoxia during Development

Abstract: Aberrant angiogenesis in the eye is the most common cause of blindness. The current study examined the role of interleukin-10 (IL-10) in ischemia-induced pathological angiogenesis called neovascularization during postnatal development. IL-10 deficiency resulted in significantly reduced pathological retinal angiogenesis. In contrast to the choroicapillaris where IL-10 interferes with macrophage influx, IL-10 did not prevent anti-angiogenic macrophages from migrating to the retina in response to hypoxia. Instead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
106
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 38 publications
10
106
1
Order By: Relevance
“…In support of this idea is the observation that expression of IL-1␤, which was reported to sustain microglial activation and promote microvascular injury via the release of proapoptotic repulsive semaphoring 3A from neurons (68), was significantly reduced in the miR-155 Ϫ/Ϫ mouse retinas following OIR. Likewise, the levels of IL-10, which reduces endothelial cell proliferation in response to hypoxia (69), were diminished in the mutant mice. IL-10 deficiency in mice has been shown to significantly reduce pathological retinal angiogenesis (69).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In support of this idea is the observation that expression of IL-1␤, which was reported to sustain microglial activation and promote microvascular injury via the release of proapoptotic repulsive semaphoring 3A from neurons (68), was significantly reduced in the miR-155 Ϫ/Ϫ mouse retinas following OIR. Likewise, the levels of IL-10, which reduces endothelial cell proliferation in response to hypoxia (69), were diminished in the mutant mice. IL-10 deficiency in mice has been shown to significantly reduce pathological retinal angiogenesis (69).…”
Section: Discussionmentioning
confidence: 90%
“…Likewise, the levels of IL-10, which reduces endothelial cell proliferation in response to hypoxia (69), were diminished in the mutant mice. IL-10 deficiency in mice has been shown to significantly reduce pathological retinal angiogenesis (69). Not only did the combined deletion of CCN1 and miR-155 reverse these effects on IL-1 and IL-10, but it also strikingly increased the expression of IL-6, which further exacerbates neovascular growth (70).…”
Section: Discussionmentioning
confidence: 90%
“…The paradigm of M1 and M2 macrophages has been studied with respect to angiogenesis. [89][90][91][92] Classical activation generates M1 macrophages, which have proinflammatory functions as we have discussed, operative during inflammation in EAU and impart tissue destruction that is effectively neutralized via blocking TNF-alpha activity. Alternatively activated M2 macrophages confer responses related to wound healing, and are capable of generating VEGF and promoting angiogenesis.…”
Section: Macrophage Conditioning Angiogenesis and Tissue Viabilitymentioning
confidence: 99%
“…As previously studied, Tregs play the immunosuppressive function through the secretion of some cytokines such as IL-10, IL-4, TGF-β, while the TGF-β may also act on tumour vascular pericytes and promote tumour angiogenesis (Gaengel et al, 2009). Recently, Dace et al (2008) found that IL -10 also promote pathological angiogenesis by regulating macrophage responses to hypoxia.…”
Section: Discussionmentioning
confidence: 94%